(untitled) (Journal of Nepal Physical Society, 2024)
A crucial cancer treatment radiotherapy uses high-energy photon beams to efficiently destroy cancerous cells. Dispersed radiation however endangers healthy tissues and compromises the effectiveness and safety of treatment. Using 6 MV and 15 MV photon beams, this study assesses dose equivalency and scattered radiation percentages to enhance patient safety and clinical results. The impact of scattered radiation and mitigation techniques are revealed by a thorough literature review. Important results are emphasized from data analysis of exposure levels Hp(10) values and percentages of scattered radiation at different field sizes and distances for 6 MV and 15 MV photon beams. Among the most significant findings is the direct correlation between exposure and dose equivalent (Hp(10)) wherein values increase in proportion to increased exposures. The percentage of scattered radiation typically decreases as exposure increases highlighting a lower risk at greater separations from the radiation source. To reduce scattered radiation and improve treatment precision the study emphasizes how crucial it is to choose the ideal beam energies and distances. To further improve radiotherapy outcomes future research should concentrate on sophisticated dosimetric techniques and customized treatment planning. To ensure safer and more effective cancer treatments this research offers significant insights for improving radiotherapy protocols.